BATA BETON BERLUBANG DARI ABU BATUBARA (FLY ASH DAN BOTTOM ASH) YANG RAMAH LINGKUNGAN - Sulistyowati, Nurul Aini (Semarang State University, 2013)
Coal ash (fly ash and bottom ash) is the waste produced by industries that use coal as a fuel source energy. Currently, the textile industry in Pekalongan city has been using coal fuel. Coal combustion waste if not dealt with seriously will be caused of environmental problems. These problems can be overcome by utilizing coal combustion waste in the manufacture of hollow block. This research uses experimental methods of making cube mortar 5 cm x 5 cm x 5 cm and hollow block 10 cm x 19 cm x 39 cm. Composition of the mix used to cube mortar 1 PC : 8 aggregate (sand + coal ash) with aggregate percentage of 4 variations. The aggregate percentages with optimum compressive strength used to manufacture of hollow block. The compressive strength tested on age 7, 14, 21 and 28 days with repetition as much as 5 times. Testing outcomes showed that hollow block manufacture with aggregate percentages in 20 % sand + 60 % bottom ash + 20 % fly ash has compressive strength 24.15 kg/cm2 and included to IV quality and its product may be utilized for non-structural wall. TCLP test showed that hollow block using fly ash and bottom ash are classified as B3 waste has a test value below the quality standards of established by the government.Abu batubara (fly ash dan bottom ash) merupakan limbah yang dihasilkan oleh industri yang menggunakan bahan bakar batubara sebagai sumber energi. Pada saat ini industri tekstil di Kota Pekalongan telah menggunakan bahan bakar batubara. Limbah pembakaran batubara bila tidak ditangani dengan serius berpotensi menimbulkan permasalahan lingkungan. Permasalahan tersebut dapat diatasi dengan memanfaatkan limbah pembakaran batubara dalam pembuatan bata beton berlobang. Penelitian ini menggunakan metoda eksperimen pembuatan mortar kubus 5 cm x 5 cm x 5 cm dan bata beton berlobang 10 cm x 19 cm x 39 cm. Komposisi campuran mortar kubus 1 PC : 8 agregat (pasir+abu batubara) dengan persentase agregat sebanyak 4 variasi. Persentase agregat dengan kekuatan tekan tertinggi digunakan dalam pembuatan bata beton berlobang. Pengujian kekuatan tekan pada umur 7, 14, 21 dan 28 hari dengan ulangan sebanyak 5 kali. Hasil pengujian menunjukkan bahwa bata beton berlobang dengan persentase agregat 20 % pasir + 60 % bottom ash + 20 % fly ash mempunyai kekuatan tekan sebesar 24,15 kg/cm2 termasuk kedalam mutu IV dan dapat digunakan untuk dinding non struktural. Uji Total Characteristic Leaching Procedure (TCLP) memperlihatkan bahwa bata beton berlobang yang menggunakan fly ash dan bottom ash yang tergolong limbah B3 mempunyai nilai uji dibawah ambang batas baku mutu yang ditetapkan oleh pemerintah.